Socialisation and experience of living in orphanages during childhood - Ainur Sadyrova; Zhomart Simtikov (International Journal of Child Care and Education Policy)
Abstract This study was aimed at investigating the processes of socialisation and development of life skills of children from orphanages in the Republic of Kazakhstan. The study used a mixed-methods approach, including structured surveys for 200 orphanage graduates and in-depth interviews with 12 field specialists. This approach provided quantitative data on socialisation experiences and life skill development, as well as qualitative insights on the effectiveness of the current assistance programs. The results of the survey of graduates of orphanages showed that children began to be brought up in orphanages from the age of 1–15 years, and the average age of the beginning of stay in an orphanage was 7.27 years. The availability of work skills among graduates was also investigated: 64% of respondents studied cooking, 42.5%—repair and carpentry, and 69.5%—sewing and knitting. Gender analysis showed that girls were more likely to learn sewing and cooking, while boys were more likely to learn repair and carpentry. About half of the children have never attended classical music concerts and ballet. The research emphasizes the need for individualized support, mentorship, and expanded cultural programs to improve socialization. Practical recommendations include targeted support programs focussing on vocational training, psychological support, and gender education.